PERENCANAAN KEGIATAN REKLAMASI PADA DISPOSAL AREA PT. ANDALAS NUSA INDAH (ANI) SUNGAI BERINGIN, KECAMATAN PELEPAT, KABUPATEN MUARO BUNGO, PROVINSI JAMBI - Arief Dwi Purnomo; Yunasril Yunasril; Heri Prabowo (Departemen Teknik Pertambangan FT UNP, 2018)
PT. Andalas Nusa Indah (PT ANI) is a coal mining company located in SungaiBringin Village, Pelepat District, Bungo Regency, Jambi Province with license status ofProduction Operation Mining License (20010-2019) based on SK Bungo IUP NO. 273 /DESDM in 2010, issued by Bungo Regent with a total area of 146 Ha.PT. ANI has a disposal with an area of ± 2.56 Ha, which has no longer functioning.The disposal of the area is in arid condition which when the dry season causes dust and inthe rainy season there are puddles so that the water puddle can overflow and drain the mineroad which productivity muddle. And also Most of the disposal land has not been usedoptimally because there is overburden pile part that is too high while the available land fordisposal is still wide. The company plans to reclaim the disposal of the area. Therefore, goodreclamation planning should be made.Reclamation planning starts from the arrangement of the land, where overburdenheap that is not equal to height will be flattened so that all the height parallel, After thatmaking terracing, topsoil top soil spread as planting medium. After the land settlement iscompleted then the land will be done cover crop planting. Furthermore, the revegetationprocess starts from pengajiran, excavation planting hole, planting, and maintenance (1 yearafter the seedlings are planted).Based on calculations in the planning of reclamation disposal area by way ofrevegation, the direct cost for the activities of land smoothing up to revegetation at thedisposal area is Rp. 132.294.402 and indirect costs of Rp. 47.301.493. Then the total cost ofrevegetation is Rp.179.595.895.